Ondansetron does not prevent physical dependence in patients taking opioid medications chronically for pain control. (1st February 2018) - Chu, Larry F.; Rico, Tom; Cornell, Erika; Obasi, Hannah; Encisco, Ellen M.; Vertelney, Haley; Gamble, Jamison G.; Crawford, Clayton W.; Sun, John; Clemenson, Anna; Erlendson, Matthew J.; Okada, Robin; et al.
Graphical abstract: Highlights: We explored using ondansetron to prevent physical dependence to chronic morphine use. After a month of morphine therapy with or without ondansetron, withdrawal was induced. Objective and subjective withdrawal scores suggest no disparity between treatment groups. Ondansetron does not prevent dependence in regular users of morphine for pain management. Abstract: Objectives: In this study, we investigated the co-administration of ondansetron with morphine, and whether it could prevent the development of physical dependence in patients taking opioids for the treatment of chronic pain. Methods: A total of 48 chronic back pain patients (N = 48) participated in this double-blinded, placebo-controlled, randomized study. Patients were titrated onto sustained-release oral morphine and randomized to take 8 mg ondansetron or placebo three times daily concurrently with morphine during the 30-day titration. Following titration, patients underwent Naloxone induced opioid withdrawal. Opioid withdrawal signs and symptoms were then assessed by a blinded research assistant (objective opioid withdrawal score: OOWS) and by the research participant (subjective opioid withdrawal score: SOWS). Results: We observed clinically significant signs of naloxone-precipitated opioid withdrawal in all participants (ΔOOWS = 4.3 ± 2.4, p < 0.0001; ΔSOWS = 14.1 ± 11.7, p < 0.0001), however no significant differences in withdrawal scores were detected between treatment groups. Conclusion: We hypothesized that ondansetron would prevent the development of physical dependence in human subjects when co-administered with opioids, but found no difference in naloxone-precipitated opioid withdrawal scores between ondansetron and placebo treatment groups. These results suggest that further studies are needed to determine if 5HT3 receptor antagonists are useful in preventing opioid physical dependence.